(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In the article, the main foundations of physical rehabilitation in the socialization of children with visual impairments affect the life expectancy of persons with developmental disabilities. They try to move, communicate less with others. This naturally leads to secondary developmental disorders, they become passive, introverted and have difficulty integrating with their peers. The above determines the importance and significance of the study of physical rehabilitation in the socialization of children with developmental disorders and the definition of the main foundations that must be taken into account when organizing and implementing this work with children with developmental disorders. This will become the basis for active involvement of these children in the socialization and every day active life. This defines the relevance of the studied problem, its theoretical, practical and social significance.